Rendahnya Integrasi Kecerdasan Emosional dan Spiritual dalam Pendidikan Agama Kristen: Kajian Filipi 1:9-10 - Lista Demensi Buana; Hermin Pindan; Filadelvia Randan; Febrianti Magi; Icha Parante (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2026)
This study examines Philippians 1:9-10 as a theological foundation for integrating emotional and spiritual intelligence in Christian Religious Education (CRE). The background reveals that CRE in Indonesia primarily focuses on cognitive knowledge transfer, often overlooking the development of emotional and spiritual intelligence. This study aims to explore how Philippians 1:9-10 can provide a biblical framework for combining these two dimensions of intelligence in CRE. The research method used is biblical exegesis with a qualitative approach, supported by a literature review. The findings suggest that Philippians 1:9-10 highlights three integrated dimensions: love (emotional-affective), knowledge (cognitive), and discernment (spiritual-reflective). These dimensions, when integrated, offer a holistic model for CRE that nurtures students comprehensively. The study’s implications call for a reformed CRE curriculum that systematically incorporates emotional and spiritual intelligence, with teaching practices that model Christ’s humility, love, and obedience. This holistic approach can enhance the formation of Christian character, promoting not only intellectual growth but also emotional maturity and spiritual depth in students.